2016
DOI: 10.2217/pmt-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatments to Counter Sleep Dysfunction as a Pathogenic Stimulus of Fibromyalgia

Abstract: Fibromyalgia is characterized by chronic widespread pain, fatigue and nonrestorative sleep. Polysomnography showed reduced short-wave sleep and abnormal alpha rhythms during nonrapid eye movement sleep in patients with fibromyalgia. However, sleep dysfunction might be pathogenic in fibromyalgia since myalgia and fatigue could be induced in healthy individuals by disrupting sleep. Poor sleep quality was a major risk factor for the subsequent development of chronic widespread pain in healthy pain-free individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…In contrast, the FM and Depressive groups did not differ in their depressive and anxious symptoms, although the FM group exhibited worse sleep quality than the Depressive group. This finding was in line with Choy [ 57 ], who suggested that sleep dysfunction might be pathogenic in fibromyalgia. This is also important because it has been identified as one of the main domains interfering with patient quality of life [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the FM and Depressive groups did not differ in their depressive and anxious symptoms, although the FM group exhibited worse sleep quality than the Depressive group. This finding was in line with Choy [ 57 ], who suggested that sleep dysfunction might be pathogenic in fibromyalgia. This is also important because it has been identified as one of the main domains interfering with patient quality of life [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Anxiety, which is a key symptom in fibromyalgia, is associated with higher levels of pain and neuropsychological disorders in these patients [18]. It is also associated with higher fibromyalgia impact, and patients with high levels of anxiety usually present an increased risk of severe fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
“…Duloxetine and MLN are dual reuptake inhibitors which are proposed to increase norepinephrine and serotonin signaling in the descending pain pathways, resulting in inhibition of pain signaling in the CNS 7 . These drugs are used to relieve pain, fatigue, and sleep problems; however, they are prescribed at doses lower than those used for the treatment of depression 8 …”
Section: Introductionmentioning
confidence: 99%
“…however, they are prescribed at doses lower than those used for the treatment of depression. 8 Both PGB and MLN have mechanisms of action that may be potentially complementary to each other in the treatment of FM; 9,10 however, they have low risk for drug-drug pharmacokinetic interactions. 11,12 In addition, this combination has not been vastly and thoroughly explored.…”
mentioning
confidence: 99%